2014
DOI: 10.1088/0957-4484/25/43/435703
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopy of graphene quantum dots: temperature effect at different excitation wavelengths

Abstract: This paper reports a comprehensive study of temperature dependence of fluorescence spectroscopy of graphene quantum dots at different excitation wavelengths. Very significant (more than 50%) and similar decrease of normalized spectrum intensity is observed within temperature range less than 80 °C for excitation wavelengths of 310 nm, 340 nm and 365 nm. Besides, the temperature dependence of the red-shift of spectrum peak shows different wavelength dependence characteristic with coefficient as high as 0.062 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…29,30 The infrared absorption spectra of cobalt (II) chloride in the 700-1500 cm −1 region has been reported by several researchers. 33,34 The cobalt (II) chloride-doped GQDs exhibit a characteristic peak between 500 and 1000 cm −1 corresponding to the presence of cobalt (II) ions (Co 2+ ) in doped GQDs. 35 Furthermore, a few strong peaks at 1097 and 1389 cm −1 (C-O carboxyl or carbonyl stretching vibrations or O-H deformation in the C-OH group) and 1639 cm −1 were seen in cobalt (II) chloride results reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 The infrared absorption spectra of cobalt (II) chloride in the 700-1500 cm −1 region has been reported by several researchers. 33,34 The cobalt (II) chloride-doped GQDs exhibit a characteristic peak between 500 and 1000 cm −1 corresponding to the presence of cobalt (II) ions (Co 2+ ) in doped GQDs. 35 Furthermore, a few strong peaks at 1097 and 1389 cm −1 (C-O carboxyl or carbonyl stretching vibrations or O-H deformation in the C-OH group) and 1639 cm −1 were seen in cobalt (II) chloride results reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene quantum dots (GQDs), emerged as novel materials in the recent decade, and have demonstrated superiority in numerous privileged properties [1]. GQDs are considered superior due to facile preparation methodologies, low toxicity, high luminescent properties and high photostability against photobleaching and blinking, which have attracted substantial attention [2][3][4][5][6][7]. GQDs have been widely employed in many applications such as the detection of proteins [8], nucleic acids [9,10], inorganic ions [11,12], small organic molecules [13,14] and biological imaging [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the temperature dependent fluorescence studies of the selected CDs were done by recording the corresponding emission profile at different temperature ranging from 10 to 70°C with an increment of 5°C each time. Results suggested that with increase in temperature, Cys based CDs showed decrease in their emission intensity; possibly due to increase in the nonradiative decay rate, resulting in decreased quantum efficiency and corresponding fluorescence intensity. , However, the trend was found to be reverse for OPD based CDs, where increase in the temperature, also increased the fluorescence emission intensity of the respective CDs. The increase in fluorescence intensity with increasing temperature might have originated from a carrier transfer mechanism between the N-dopant induced state (energy level) and emitting state of CDs .…”
Section: Resultsmentioning
confidence: 98%